Teaching receptive naming of Chinese characters to children with autism by incorporating echolalia. - Leung, J P (1997)
The facilitative effect of incorporating echolalia on teaching receptive naming of Chinese characters to children with autism was assessed. In Experiment 1, echoing the requested character name prior to the receptive naming task facilitated matching a character to its name. In addition, task performance was consistently maintained only when echolalia preceded the receptive manual response. Positive results from generalization tests suggested that learned responses occurred across various novel conditions. In Experiment 2, we examined the relation between task difficulty and speed of acquisition. All 3 participants achieved 100% correct responding in training, but learning less discriminable characters took more trials than learning more discriminable characters. These results provide support for incorporating echolalia as an educational tool within language instruction for some children with autism.